ANALISIS KRITIS PEMIKIRAN KHR. AS’AD SYAMSUL ARIFIN TENTANG NEGARA, SISTEM PEMERINTAHAN DAN PENERIMAAN AZAS TUNGGAL PANCASILA - Ahmad Ahmad; Hasbi Ash Shiddiqi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research will focus on the study of KHR Thought. As'ad Syamsul Arifin on the State System and the System of Government in Islam which is stated in the form of Acceptance of the Single Principle of Pancasila. This study wants to answer First; how does KHR think. As'ad Syamsul Arifin on the State System and the System of Government in Islam. Second; how KHR thinks. As'ad Syamsul Arifin about accepting Pancasila as a Single Principle. Methodology This research uses qualitative research with a conceptual and historical approach. Primary data sources are the book al-ahkam as-Sulthoniyah and the book Biography of KHR. As'ad Syamsul Arifin, MUnas ALim Ulama' Situbondo Document in 1983. The data collection technique in this study is documentation. Meanwhile, the data analysis technique carried out in this study is descriptive-interpretive. The results of this study show that KHR Thinking. As'ad Syamsul Arifin on the State System and the System of Government in Islam which is stated in the form of Acceptance of the Single Principle of Pancasila. KHR's thoughts. As'ad Syamsul Arifin on the State System and the System of Government in Islam was obtained comprehensively and completely from his contact with Hadlrotus Shaykh KH. Hasyim Asy'ari, as well as his real work in defending and contributing to the nation's journey. Standing as a Fighter for the Jihad Resolution, against the Japanese, taking part as a Constituent Member, Fighting against the PKI, and directly involved as a Politician. Meanwhile, KHR's thoughts. As'ad Syamsul Arifin about accepting Pancasila as a Single Principle is the culmination of his thoughts on the State System and the System of Government. According to Kiai As'ad, the first precept of Pancasila is a reflection of the teachings of monotheism in Islam. Not stopping here, Kiai As'ad boldly presented his views and direct criticism to President Soeharto who wanted to make Pancasila a tool to generalize the truth of all religions. This research contributes to strengthening the mapping of the role and contribution of Kiai Pesantren in the concept of the State and the Government system. The research has not reached the aspect of KHR thinking. As'ad Syamsul Arifin which is outlined in works/books/manuscripts.